The Princess in Black and the hungry bunny horde - Hale, Shannon; Hale, Dean, 1972- (Hale, Shannon. Princess in Black, 2016)
"Princess Magnolia and her unicorn, Frimplepants, are on their way to have brunch with Princess Sneezewort, an occasion Frimplepants enjoys more than anything in the world. But just when he can smell the freshly baked bread and the heaping platters of sugar-dusted doughnuts, Princess Magnolia's glitter-stone ring rings. The monster alarm! After a quick change in the secret cave, Princess Magnolia and Frimplepants are transformed into the Princess in Black and her faithful pony, Blacky. But when they get to the goat pasture, all they can see is a field full of darling little bunnies nibbling on grass, twitching their velvet noses, and wiggling their fluffy tails. Where are the monsters? Are these bunnies as innocent as they appear?"--